PENERAPAN MODEL PEMBELAJARAN AKTIF KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMA NEGERI 1 KOTO GASIB - Puspa Budhi Asih Budhi Asih; Johni Azmi Azmi; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The aim of this research is to know the effect of arisan card active learning toward student achievement on chemical bonds material class X MIA of 1 Senior High School Koto Gasib. Form of research is experiment research with randomized group pretest-posttest design. The sample of this research is two groups randomly determined after normality test and homogeneity test, class X MIA 2 as the control class and as the experiment class is X MIA 1. Experiment group is a group that is treated with implementing arisan card active learning. Data analysis technique that used in this research is the t-test. Based on the final results of data process obtained tarithmetic ≥ ttable (3,013 ≥ 1,67) means that the application of arisan card active learning can improve student achievement on the subject of chemical bonds at class X MIA of 1 Senior High School Koto Gasib. The calculation of effect size resulted on student achievement was 11,99%.  Key Words : Active Learning, Arisan card, Active learning, student achievement, Chemical bonds.